2006
DOI: 10.22358/jafs/66838/2006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sex and dietary antioxidants β-carotene, vitamins C and E in a CLA-enriched diet on the lipid profile and oxidative stability of pork meat

Abstract: Fifty Polish Large White growing pigs were randomly divided into 5 groups (5 gilts and 5 barrows in each group) and fattened from 50 to 105 kg body weight. The experimental factors were gender and addition of vitamins C, E and β-carotene to the diets. All diets were supplemented with 0.5% CLA. Polyunsaturated fatty acids (PUFA) were observed to decrease in pigs receiving combined vitamins C, E and β-carotene compared with pigs receiving a single supplement of β-carotene (P<0.05). In gilts the level of saturate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In agreement with several studies (Pieszka et al, 2006;Latorre et al, 2007b), sex influenced the SFA, PUFA, and UFA contents of the ham fat cover, with greater concentrations of C16:0, C18:0, and total SFA and decreased proportions of C18:2, C18:3, and total PUFA and UFA being found in B compared with G1. The increase in SW resulted in greater SFA content in gilts, mainly due to greater C16:0 concentrations.…”
Section: Subcutaneous Fat Qualitysupporting
confidence: 92%
“…In agreement with several studies (Pieszka et al, 2006;Latorre et al, 2007b), sex influenced the SFA, PUFA, and UFA contents of the ham fat cover, with greater concentrations of C16:0, C18:0, and total SFA and decreased proportions of C18:2, C18:3, and total PUFA and UFA being found in B compared with G1. The increase in SW resulted in greater SFA content in gilts, mainly due to greater C16:0 concentrations.…”
Section: Subcutaneous Fat Qualitysupporting
confidence: 92%
“…Regarding the influence of gender on fatty acid composition of subcutaneous backfat, Pieszka et al (2006) observed that in gilts fed with CLA diets, the SFA content in fat was lower and the content of PUFA, MUFA and PUFA/SFA ratio were higher than in barrows. In agreement with our results, some other experiments also reported that subcutaneous backfat from males is more saturated than that from females (Courboulay and Massabie, 1996;Smithard et al, 1980), although, Serrano et al (2008 did not observe influence of gender on fatty acid composition of subcutaneous backfat from Duroc × Iberian heavy pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the concentration of ChlOs (oxysterols) in beef and pork, which possess mutagenic, carcinogenic, and cytotoxic properties, depends strongly on the cholesterol content of their muscles [9][10][11][12]. ChlOs possess numerous adverse biological effects and play an important role in the development of atherosclerosis [12,13].…”
Section: Introductionmentioning
confidence: 99%